EVALUATING THE IMPACT OF DAY THERAPY USING ST CHRISTOPHER'S HOSPICE INDEX OF PATIENT PRIORITIES (SKIPP). Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Rayment, Clare; Gordon, Jean; Lepp, Lydia
Abstract : Aims: To evaluate patients' perceived global impact of day therapy and the impact of day therapy on patients' quality of life (QOL) and concerns using SKIPP. Methods: SKIPP was completed at a patients' second attendance and thereafter 6 weekly for all new patients attending day therapy at Marie Curie Hospice, Bradford between January and July 2013. Results: 43 new attendees: 39 completed SKIPP. 24 completed one SKIPP, 15 two and 5, three. 28 patients continue to attend, 7 have died and 4 were discharged. SKIPP was completed by patients alone or with staff. Data was missing for SKIPP one for 9 patients. Average QOL, on a 1–7 (excellent) score, at SKIPP one was 3, SKIPP two, 5, and SKIPP three, 6. At SKIPP one, 77% of patients felt day therapy had improved things for them: 8% felt it had not helped much and 5% didn't know. At SKIPP two these figures had changed to 87% felt day therapy had helped: 13% not at all. At SKIPP three, 4 patients felt it had helped to a very great extent, 1 not at all. At SKIPP two, 10 felt that day therapy had made their concern better, 3 had no change and 2 felt it was a little worse. At SKIPP three, 3 patients felt their concern was better, 1 much worse and data was missing for 1 patient. Conclusions: SKIPP demonstrates that average QOL improves during day therapy attendance and most patients' think day therapy is helping them overall. However, a third of patients' main concern remained the same or a little worse at SKIPP 2. Only a small number completed a second SKIPP and this will influence the results. SKIPP appears to be useful in demonstrating the benefits of day therapy for some aspects of patient care.